Online CD Library Management System / Chan Peng Lian - Chan, Peng Lian (2005)
The web based Online CD Library Management System (OCDLib) is a web based system which serves as a platform to assist user, such as student, lecturer and administrator in using their library efficiently and effectively. OCDLib consist of nine modules and is basically divided into 3 target users which are non-register member, register member and administrator. The module are login module, registration module, search and reserve module, user profile module, user guide module, loan module, return module, maintenance module and report module. Login module is provided to validate the user identity. The methodology used in developing the OCDLib is incremental model. This methodology give a clear picture of what is going on during the development of the system which able to track the time limitation along the way of completing this system. A lot of backtracking and iteration occurred to ensured any error correction as the development progress. The method used in collecting information for completing this proposed system are through library research, interview with Information System (IS) staff. internet research and survey. OCDLib is developed using ASP .Net, The system runs on Window XP using Internet Information Server (IS) as the web server and SQL server as the database management The designing tools used include Adobe Photoshop and Macromedia Flash. OCDLib coding is written using modular and top down approach. The system is written module by module to debug nad trace error. External and internal document are practiced to reduce coding error and facilitate coding maintenance. Unit testing, module testing. integration testing and system testing are applied to test the effectiveness and efficiency of OCDLib. Toward the end of completion, OCDLib is evaluated system strength and weaknesses are identified and future enhancements are suggested. It can be concluded that OCDLib has achieved its requirement with additional function to meet the need of an informational system and as well as management information system.